Chest compressions quality during sudden cardiac arrest scenario performed in virtual reality: A crossover study in a training environment. Issue 48 (25th November 2020) - Jaskiewicz, Filip; Kowalewski, Dawid; Starosta, Katarzyna; Cierniak, Marcin; Timler, Dariusz
Abstract : Abstract: Potential attributes of virtual reality (VR) can be a breakthrough in the improvement of sudden cardiac arrest (SCA) training. However, interference with the virtual world is associated with the need of placing additional equipment on the trainee's body. The primary aim of the study was to evaluate if it does not affect the quality of chest compressions (CCs). 91 voluntarily included in the study medical students participated twice in the scenario of SCA – Traditional Scenario (TS) and Virtual Reality Scenario (VRS). In both cases two minutes of resuscitation was performed. If VRS was the first scenario there were significant differences in CCs depth (VRS - Me = 47 mm [IQR 43 – 52] vs TS - Me = 48 mm [IQR 43 – 55]; P = .02) and chest relaxation (VRS - Me = 37% [IQR 5 – 91] vs TS - Me = 97% [IQR 87 – 100]; P < .001). 97.8% of respondents believe that training with the use of VR is more effective than a traditional method ( P < .01). Most of the study group (91%, P < .01) denied any negative symptoms during the VR scenario. Virtual reality can be a safe and highly valued by medical students, method of hands-on CPR training. However additional VR equipment placed on the trainee's body may cause chest compressions harder to provide. If it is not preceded by traditional training, the use of VR may have an adverse impact on depth and full chest relaxation during the training. To make the best use of all the potential that virtual reality offers, future studies should focus on finding the most effective way to combine VR with traditional skill training in CPR courses curriculum.